The Effect of Peer Education of Bone Health on Knowledge Level of High School Students - Muhamad Ivan; Muhammad Nurhuda; Ade Teti Vani (Journal on Education, 2023)
The goal of this investigation is to ascertain how peer education about bone health affects students' knowledge. A one-group pre-test-post-test design was used in the pre-experimental study design. Twenty-nine students were chosen as the sample for this study using a straightforward random sampling procedure. 27 questions about bone health were included in the questionnaire that served as the study tool. The t-test statistical test was used for univariate and bivariate data analysis. According to the findings, there was a significant difference in knowledge between the two time periods before and after the peer education intervention for bone health (p-value = 0.000). The obtained beta squared value was 0.89, which indicated that peer education interventions for bone health had a significant impact on knowledge growth. A similar study will be conducted in the future to assess attitudes and behavior, as well as the presence of a control group.